Green dome / Ahmad Haikal Ahmad Danial ... [et al.] - Ahmad Danial, Ahmad Haikal; Mod Zahari, Ilham Hafeezie; Saiful, Nur Aliyah Humairah; Jamaludin, Nazrul Helmy (2024)
Green Dome is a pavilion dome made of mainly timber and glasses which are perfect for relaxing, leisure and sightseeing. It has seating areas for a group of people especially students for them to have discussion, works or hanging out. It can be used for small events such as socialising, exhibition and such. UiTM students and staffs are our target customer but it is also open for public purchase. It’s tranquility is what the attraction of this Green Dome is. There is a bench located in the centre of Green Dome where the occupants can access to full view inside the dome where it is adorned with pole that has hanging plants. There are some gardens inside the dome where plants and trees are planted. The Green Dome is prepared with wall fans and lighting to ensure the convenience of the users.